2010
DOI: 10.1246/bcsj.20100094
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Analyses of Amyloid β Peptide (1–40) with Glycosaminoglycan Model Polymers

Abstract: We synthesized a novel glycopolymer library with 6-sulfo-GlcNAc and glucuronic acid (GlcA) based on the structure of glycosaminoglycans. The molecular weights of the polymers were controlled via living radical polymerization. The interactions of A¢ (140) with glycopolymers were analyzed by inhibition activity of protein aggregation using ThT fluorescence assay, atomic force microscopy observation, and CD spectra. The inhibition activity of A¢ was much affected by the sugar structure and molecular weight of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Miura and coworkers found that lower molecular weight heparin mimics were able to inhibit amyloid-beta aggregation better than the higher molecular weight heparin mimics. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Miura and coworkers found that lower molecular weight heparin mimics were able to inhibit amyloid-beta aggregation better than the higher molecular weight heparin mimics. 25 …”
Section: Introductionmentioning
confidence: 99%
“…No noticeable changes in the peptide structure were observed upon peptide/heparin complex formation. However, a weaker intensity of CD bands of bound ECL2 and Nt, which was also seen for other heparin‐binding peptides, can indicate their strong interaction with the glycosaminoglycan . Since the addition of HFIP does not influence the conformation of heparin, it was possible to evaluate the conformational changes in the peptides upon heparin binding by the subtraction of its CD spectrum from the CD spectra of the complexes (Figure B and 2C).…”
Section: Resultsmentioning
confidence: 98%
“…The second step of the synthesis, the coupling between 1a and b and acryloyl chloride, was also conducted in aqueous solution without isolating 1a and b . The amino group selectively reacted with acryloyl chloride in aqueous solution because the nucleophilicity of amino group was higher than those of hydroxy group and water . After the first step reaction, the reaction mixture was washed with chloroform to thoroughly extract excess 4‐aminobenzentiol and was directly added with acryloyl chloride to yield 2a and b (Table ).…”
Section: Resultsmentioning
confidence: 99%